Flavonoids-Rich Plant Extracts Against Helicobacter pylori Infection as Prevention to Gastric Cancer - Ivyna de Araújo Rêgo, Renaly; Guedes Silvestre, Geovana Ferreira; Ferreira de Melo, Demis; Albino, Sonaly Lima; Pimentel, Marcela Monteiro; Silva Costa Cruz, Sara Brito; Silva Wurzba, Sabrina Daniela; Rodrigues, Wellington Francisco; Goulart de Lima Damasceno, Bolívar Ponciano; Cançado Castellano, Lúcio Roberto (Frontiers in Pharmacology, 2022)
Gastric cancer is the fifth most common and fourth type to cause the highest mortality rates worldwide. The leading cause is related to Helicobacter pylori (H. pylori) infection. Unfortunately, current treatments have low success rates, highlighting the need for alternative treatments against carcinogenic agents, specifically H. pylori. Noteworthy, natural origin products contain pharmacologically active metabolites such as flavonoids, with potential antimicrobial applications. Objective: This article overviews flavonoid-rich extracts' biological and pharmacological activities. It focuses on using these substances against Helicobacter pylori infection to prevent gastric cancer. For this, PubMed and Science Direct databases were searched for studies that reported the activity of flavonoids against H. pylori, published within a ten-year time frame (2010 to August 2020). It resulted in 1,773 publications, of which 44 were selected according to the search criteria. The plant family primarily found in publications was Fabaceae (9.61%). Among the flavonoids identified after extraction, the most prevalent were quercetin (19.61%), catechin (13.72), epicatechin (11.76), and rutin (11.76). The potential mechanisms associated with anti-H. pylori activity to the extracts were: inhibition of urease, damage to genetic material, inhibition of protein synthesis, and adhesion of the microorganism to host cells. Conclusion: Plant extracts rich in flavonoids with anti-H. pylori potential proved to be a promising alternative therapy source, reinforcing the relevance of studies with natural products.